The Power of Promise : Examining Nuclear Energy in India - Ramana, M. V. (New Delhi Viking, 2012)
Examining different aspects of India's nuclear energy program and the claims of success made on its behalf, M.V. Ramana makes a historically nuanced and compelling argument as to why it has failed in the past and why its future is dubious.
Include Appendices, References and Index.
Examining Nuclear Energy in India.
Keywords: Nuclear energy -- Nuclear energy--Government policy -- India